1990
DOI: 10.1021/ac00200a010
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of carbon-13 nuclear magnetic resonance spectra. Identification and quantification of average structures in petroleum distillates

Abstract: The jC10, C^, ..., C25) fractions from two North Sea crude oils are investigated. For each fraction CH" ( = 1, 2, 3) 13C nuclear magnetic resonance subspectra are obtained with the use of distortionless enhancement by polarization transfer subspectral editing. The combined spectral profiles for each fraction, consisting of 9651 data points, are reduced to 1024 pooled variables by using a "soft" maximum entropy criterion. A principal component analysis is performed. Two principal components account for 85.9% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The incorrectly assigned samples A and E are actually both livers. In a previous study ( 1 4 ) it has been found that livers form diffuse clusters and as a class are more widely spread than other types of tissues. This may account for the two incorrectly classified unknowns.…”
Section: Classification Resultsmentioning
confidence: 93%
“…The incorrectly assigned samples A and E are actually both livers. In a previous study ( 1 4 ) it has been found that livers form diffuse clusters and as a class are more widely spread than other types of tissues. This may account for the two incorrectly classified unknowns.…”
Section: Classification Resultsmentioning
confidence: 93%
“…Instead of submitting the precipitate to chromatographic fractionation, the 13 C-NMR spectrum of the complex mixture was recorded. Indeed, 13 C-NMR spectroscopy is an alternative technique that has been successfully employed in the identification of the individual components of organic mixtures, namely alkanes in petroleum distillates (Brekke et al, 1990), triglycerides in vegetable oils (Gunstone, 1991), terpenes in essential oils (Formácek and Kubeczka, 1982), and sugars in pine leaf extracts (Blunt and Munro, 1976). In our laboratories, a computerised procedure that allows the identification of components of natural mixtures has been developed and applied to several families of compounds including phenols in bio-oils (Bighelli et al, 1994), sugars in honey (Mazzoni et al, 1997), and terpenes in essential oils, solvent extracts and resins (Tomi et al, 1995;Bradesi et al, 1996;Castola et al, 1999;Rezzi et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Classically, chemometrics is a collection of globally recognized powerful multivariate modeling tools within the realm of analytical chemistry. In other branches of the chemical sciences and especially in chemical engineering, chemometrics is not as widely practiced as it actually deserves to be. There are some examples of chemometrics in process control, quality control, , product design, and CRE …”
Section: Introductionmentioning
confidence: 99%